Answer:
a. For
→
![y=36](https://img.qammunity.org/2020/formulas/mathematics/high-school/rfqw9gq4zvliwvuokh5p7xjbyorqsrlqeb.png)
b. For
→
![y=18](https://img.qammunity.org/2020/formulas/mathematics/middle-school/vb6q7ho5yty89rik1kr6n55jrdcm4q31mu.png)
c. For
→
![y=9](https://img.qammunity.org/2020/formulas/mathematics/high-school/lbe7cetkyupszfsu17lale83fwrr9twib5.png)
d. For
→
![y=6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jhtozgvvhmtz2zmnl0yecx99jhilzs0e6k.png)
Explanation:
Since the variables "x" and "y" are inversely related, the equation has the following form:
![y=(k)/(x)](https://img.qammunity.org/2020/formulas/mathematics/high-school/yvi2252c5rayvqe4ondi5ptqpn102d8bjm.png)
Where "k" is the constant of variation.
In this case we know that:
![k=18](https://img.qammunity.org/2020/formulas/mathematics/high-school/9fq0bqyc9yypkm3aa0nrf0zhl9xk8l0p0z.png)
So, the equation is:
![y=(18)/(x)](https://img.qammunity.org/2020/formulas/mathematics/high-school/nu8lqin4cg1as01szigs0ur5k3gp1g0t6n.png)
Therefore, substituting the given values of "x" into the equation, we get:
a. For
→
![y=(18)/(0.5)=36](https://img.qammunity.org/2020/formulas/mathematics/high-school/1i5x9y0r4ivyn5b005cc6dfx66fvtozir2.png)
b. For
→
![y=(18)/(1)=18](https://img.qammunity.org/2020/formulas/mathematics/high-school/a9q5apz2wppwnspsdmcb9nw1lwz778r0jy.png)
c. For
→
![y=(18)/(2)=9](https://img.qammunity.org/2020/formulas/mathematics/high-school/d6rq8t1s5w4nhyxe83hdz5eb3lgv1955kv.png)
d. For
→
![y=(18)/(3)=6](https://img.qammunity.org/2020/formulas/mathematics/high-school/sj1dqtolei74cc3a0ygn0cx99ldnr0p0e4.png)